Yes-associated protein is dysregulated in human congenital diaphragmatic hernia patients during mid and end gestation - Miyake, Yuichiro; Jank, Marietta; Patel, Daywin; Ozturk, Arzu; Aubert, Ophelia; Ai, Xingbin; Yamataka, Atsuyuki; Keijzer, Richard (Pediatric surgery international, 2025)
Background Yes-associated protein (YAP) is implicated in congenital diaphragmatic hernia (CDH). This study aims to investigate the abundance of YAP and its inactive form, phosphorylated YAP (p-YAP), in fetal human lung tissues from CDH cases compared to control cases at mid-gestation and end-gestation. Methods Immunofluorescence was performed to assess the abundance of YAP and p-YAP in lung tissues from human CDH and control fetuses who died from causes other than CDH. Additionally, the impact on cellular differentiation was evaluated by assessing the expression of Homeodomain-only protein X (HOPX) and Surfactant protein C (SPC). Results Immunostaining revealed a higher abundance of YAP and p-YAP in both mid-gestation and end-gestation lung tissues. Notably, the abundance of p-YAP was increased in CDH tissues compared to controls, indicating higher levels of the inactive form of YAP in CDH. HOPX and SPC staining showed CDH tissues had a higher number of SPC-positive cells and fewer HOPX-positive cells at end-gestation. Conclusions Our findings suggest that in CDH, YAP is predominantly present in its inactive form, p-YAP, potentially disrupting normal lung development and differentiation. This underscores the potential involvement of YAP dysregulation in the pathogenesis of CDH.
Online veröffentlicht: 02. Dezember 2024
Gesehen am 15.04.2025